Evaluation of the effect of oral ritodrine on implantation rate in in-vitro fertilization-embryo transfer cycles - Maryam Ahmadi; Marziyyeh Farimani; Soghra Rabiee (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Pregnancy rate with IVF cycle is almost 22%. Many investigations perform to increase this rate in IVF. Various factors affect the result of IVF cycles. One of these factors could be uterine contractions that expel transferred embryo. Ritodrine is a beta mimetic agent that can block and decrease uterine contractions.Objective: The objective of this study was to determine ritodrine effectiveness for increasing the implantation rate in IVF cycles, and its probable mechanisms in decreasing uterine contractions as well.Materials and Methods: A total of 100 patients of IVF-ET cycles were divided randomly in two groups in a university hospital, Hamadan, Iran. The case group were prescribed ritodrine 10 mg / bid orally after oocyte retrieval until 10 days. The control group didn't received ridotrine.Results: In ritodrine group 14% of patients and in control group 16% had positive β-hCG test (p-value>0.5).Conclusion: Ritodrine did not improve the implantation rate in IVF-ET cycles